2014
DOI: 10.1016/j.pragma.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The dialogical dimension of intonational meaning: Evidence from French

Abstract: The aim of this study was to test if the meaning of intonational contours involves speaker commitment and attitude attribution to the addressee. We examined whether the pragmatic choice of a contour signals how the speaker (S) anticipates the reaction of the addressee (A) to his utterance by attributing attitudes to him and calling for his next move. We focused on four French contours (a fall L*L%, a rise H*H%, a rise-fall H*L% and a rise-fall-rise H+!H*H%). In an original forced-choice interpretation task, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…In more recent accounts, which build on Post's treatment of H+H*, this contour has been labeled for model-internal reasons as L H+!H* !H% by Delais-Roussarie et al (2015) (who unlike Post, 2000, do not assume an automatic downstep rule), or as L H+L* L% by Portes and Beyssade (2015) and by Sichel-Bazin (2015). Note that Delais-Roussarie et al provide no explicit motivation for labeling the boundary tone as !H% rather than L%, which descriptively corresponds to a final low f0 (see, e.g., Delais-Roussarie et al, 2015, Figure 3.12).…”
Section: Phonetics and Phonology Of Penultimate Rise-falls In Continementioning
confidence: 99%
See 2 more Smart Citations
“…In more recent accounts, which build on Post's treatment of H+H*, this contour has been labeled for model-internal reasons as L H+!H* !H% by Delais-Roussarie et al (2015) (who unlike Post, 2000, do not assume an automatic downstep rule), or as L H+L* L% by Portes and Beyssade (2015) and by Sichel-Bazin (2015). Note that Delais-Roussarie et al provide no explicit motivation for labeling the boundary tone as !H% rather than L%, which descriptively corresponds to a final low f0 (see, e.g., Delais-Roussarie et al, 2015, Figure 3.12).…”
Section: Phonetics and Phonology Of Penultimate Rise-falls In Continementioning
confidence: 99%
“…what he says is evident, or that he does not want to commit himself" (Post, 2000, p. 137). For Delais-Roussarie et al 2015, the L H+!H* !H% contour is related to contradiction statements, while in Portes and Beyssade (2015) and Sichel-Bazin (2015), the L H+L* L% contour is associated with adamant statements. According to Sichel-Bazin, "the speaker urges the addressee to add the content of the proposition to the common ground and forget about any alternative that the addressee could have in mind" (Sichel-Bazin, 2015, p. 209).…”
Section: Interpretation Of the Contourmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have emphasized the dialogical status of intonation and the need to take into account interactive and argumentative dimensions of meaning. Portes et al showed experimentally that intonational contours in French encode information about speaker commitment and attitude attribution to the addressee. In a forced‐choice interpretation task, participants had to choose among four possible reactions ( I get it ; I've no idea ; I guess you're right ; No, really, it's true ) after hearing sentences spoken with one of four contour types, namely a fall L* L%, a rise H* H%, a rise–fall H* L%, and a rise–fall–rise H + !H* H%.…”
Section: Semantic and Pragmatic Approachesmentioning
confidence: 99%
“…Viennent ensuite les travaux sur les rapports entre intonation et fonctions discursives dans un cadre interactionniste et dialogique (i.e., les rapports entre intonation et actes de parole comme ceux étudiés parPortes et al, 2014). Sous une approche formelle, nous pouvons constater que les auteurs s'accordent sur le statut d'au moins quatre schémas intonatifs prototypiques en français qui seraient observés à la fin des groupes intonatifs (GI)5 , à savoir : montant, descendant, montant-descendant depuis la syllabe pré-tonique et montant-descendant dans la dernière syllabe.…”
unclassified